Role of oxytocin in bone - Wang, Tianming; Ye, Jianya; Zhang, Yongqiang; Li, Jiayi; Yang, Tianxiao; Wang, Yufeng; Jiang, Xiao; Yao, Qingqiang (Frontiers in Endocrinology, 2024)
Oxytocin (OT) is a posterior pituitary hormone that, in addition to its role in regulating childbirth and lactation, also exerts direct regulatory effects on the skeleton through peripheral OT and oxytocin receptor (OTR). Bone marrow mesenchymal stem cells (BMSCs), osteoblasts (OB), osteoclasts (OC), chondrocytes, and adipocytes all express OT and OTR. OT upregulates RUNX2, BMP2, ALP, and OCN, thereby enhancing the activity of BMSCs and promoting their differentiation towards OB rather than adipocytes. OT also directly regulates OPG/RANKL to inhibit adipocyte generation, increase the expression of SOX9 and COMP, and enhance chondrocyte differentiation. OB can secrete OT, exerting influence on the surrounding environment through autocrine and paracrine mechanisms. OT directly increases OC formation through the NκB/MAP kinase signaling pathway, inhibits osteoclast proliferation by triggering cytoplasmic Ca2+ release and nitric oxide synthesis, and has a dual regulatory effect on OCs. Under the stimulation of estrogen, OB synthesizes OT, amplifying the biological effects of estrogen and OT. Mediated by estrogen, the OT/OTR forms a feedforward loop with OB. Apart from estrogen, OT also interacts with arginine vasopressin (AVP), prostaglandins (PGE2), leptin, and adiponectin to regulate bone metabolism.This review summarizes recent research on the regulation of bone metabolism by OT and OTR, aiming to provide insights into their clinical applications and further research.